Analysis of Infinitive Phrases in Novel By J.K.Rowling ‘Harry Potter and the Sorcerer’s Stone’ - Niken Wulandari (Journal Corner of Education, Linguistics, and Literature, 2022)
Infinitive phrase may function, not as a main verb of a clause, but as another part of speech—either as a noun, adjective, or adverb that takes the form of “to + verb” in its simplest form. This research is done to find out the types of infinitives found in the novel written by J.K. Rowling, ‘Harry Potter and the Sorcerer’s Stone’ and the function of infinitives found in the novel written by J.K. Rowling, ‘Harry Potter and the Sorcerer’s Stone’ done by 7 students of Magister of English Education of Lampung University. This study uses a qualitative descriptive approach, and the data is taken from the novel written by J.K Rowling ‘Harry Potter and the Sorcerer's Stone’ page 1-8, 33-40, 65-72, 97-104, 129-136, 161-168, and 193-200.From the results and discussion, it can be concluded that not all students look for the same forms and classification of the infinitive, but the dominant types used in the novel is the to-infinitive.